LOCAL WISDOM VALUES GOVERNANCE AS NON-FINANCIAL INTANGIBLE ASSETS IN SUPPORTING INDIGENOUS PEOPLES' SUSTAINABILITY IN KAMPUNG PULO KABUPATEN GARUT - Suarsa, Abin; Verawaty, Verawaty; Sugihyanto, Toto (2019)
The study entitled " Local Wisdom Values Governance as Non-Financial Intangible Assets in Supporting Indigenous Peoples' Sustainability in Kampung Pulo Kabupaten Garut " aims to understand the motivation of indigenous peoples Pulo village in implementing local wisdom in life everyday so as to support its sustainability.The method used in this research is qualitative method with interpretive paradigm and phenomenological approach. The analytical unit focuses on awareness, noema, noesis, intuition, and intersubjectivity. The main data of this research are interview result and observation result.The results of this study indicate that the local wisdom of the pulo community contains the philosophy of life and the teachings that prioritize the balance between human, God, and nature. Governance emphasizes exemplary, communication, education, and mutual reminders.